Transformasi kalender Saka (Sūryasiddhānta) menuju kalender Gregorian di Jawa dan Asia Tenggara - Supriyanto, Mahathelge Ahmad (Universitas Negeri Malang, 2024)
Abstract The purpose of this article is to understand the transformation or change in the use of calendars in the Java and Southeast Asia regions. The year in the Saka calendar itself starts from the coronation day of Maharaja Kanishka I which fell in 78 AD, where that day was then referred to as the 1st day of the 1st month of the 1st year of Saka. The new year in the Saka year usually falls after the first new moon in March in the Gregorian calendar, or after the dead moon (tilem sasih) in the month of Kasanga in the Saka calendar. The Saka calendar originates from India and was adapted by the Javanese people who adhere to the Hindu-Buddhist religion. The Saka year starts from 78 AD, which is considered the year of the accession of Aji Saka, the legendary figure who brought script and civilization to Java. The Saka calendar system consists of 12 months which refers to the lunisolar system, which is a system that combines the rotation of the sun and moon.Abstrak Tujuan dari tulisan ini adalah memahami bagaimana transformasi atau perubahan penggunaan kalender yang berada pada wilayah Jawa dan Asia Tenggara. Tahun dalam kalender Saka sendiri dimulai dari hari penobatan Maharaja Diraja Kanishka I yang jatuh pada tahun 78 Masehi, di mana hari itulah yang kemudian disebut sebagai tanggal 1 bulan 1 tahun 1 Saka. Tahun baru di tahun Saka biasanya akan jatuh setelah bulan baru pertama bulan Maret kalender Masehi, atau setelah bulan mati (tilem sasih) bulan Kasanga kalender Saka. Kalender Saka berasal dari India dan diadaptasi oleh masyarakat Jawa yang menganut agama Hindu-Budha. Tahun Saka dimulai dari tahun 78 Masehi, yang dianggap sebagai tahun naik tahtanya Aji Saka, tokoh legendaris yang membawa aksara dan peradaban ke Jawa. Sistem kalender Saka terdiri dari 12 bulan yang merujuk pada sistem lunisolar, yaitu sistem yang menggabungkan perputaran matahari dan bulan.